Simulations of cell deformation in non-Newtonian fluids - Lim, Benjamin Zhiwen (Nanyang Technological University, 2021)
Microfluidic devices are used for modern medicine through bioprinting and flow cytometry for manufacturing and diagnosis purposes. Experimental methods are plenty and well developed, but simulation and modelling work in this field is still in its infancy by comparison, prompting this research project. Numerical methods involving fluid structure interaction (FSI) are used to model cell deformation in flows, with the objective of developing a working model that can capture cell deformation and translation. Two separate solvers for the structural and fluid domains were coupled and iteratively solved. Various FSI models and simulation setups using ANSYS software were developed, documented and analyzed and the experimental results were processed in parallel for numerical verification. The extent of cell deformation is quantified by a deformation index, which confirms the feasibility to emulate the compression phase of the experimental results. Non-Newtonian fluid properties were also investigated, revealing potential for modelling other cell deformation concepts. The results of the project set a solid explorative backbone for the further utilization of numerical methods for predictive analysis in flow cytometry.